Silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cable and preparation method of silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material
By constructing a dynamic crosslinking system in photovoltaic cable materials, the reaction of β-cyclodextrin, polyethylene glycol and 2,5-furandicarboxylic acid is used to generate precursors, and combined with sodium alginate, sepiolite and other materials. The problem of insufficient crack resistance of cable materials under the superposition of hot and cold impact and optical radiation aging is solved, and higher toughness and crack resistance are achieved.
Patent Information
- Application Number
- CN202411860592.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The crack resistance of photovoltaic cable materials under the superposition of hot and cold impact and optical radiation aging is insufficient, making it difficult to effectively improve.
A preparation method is adopted to form a precursor by reacting β-cyclodextrin, polyethylene glycol and 2,5-furandicarboxylic acid under an inert gas, and combined with sodium alginate, sepiolite and other materials to form a dynamic Cross-linking system to improve the toughness and crack resistance of cable materials.
It significantly improves the crack resistance of cable materials under the superposition of hot and cold impact and optical radiation aging, ensuring the reliability and durability of cables in harsh environments.
Smart Images

Figure CN119410062A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cable materials, and more specifically, to a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables and a preparation method thereof. Background Art
[0002] As the global demand for clean energy continues to grow, the photovoltaic industry is developing rapidly. Photovoltaic systems require reliable cables to transmit electricity, and the performance requirements for cable materials are getting higher and higher. Photovoltaic cables are usually exposed to outdoor environments and need to withstand various harsh conditions such as high temperature, low temperature, ultraviolet radiation, etc. Therefore, the corresponding cable materials must have good weather resistance, heat resistance, flame retardancy and aging resistance.
[0003] Traditional halogen-containing cable materials will produce a lot of smoke and toxic gases when burning, which will cause serious harm to people and the environment. In order to meet environmental protection and safety requirements, technicians have developed low-smoke halogen-free flame-retardant cable materials, which produce less smoke and low toxicity when burning. In addition, on the basis of flame retardant properties, the use of silane cross-linking technology can improve the heat resistance, aging resistance and mechanical strength of polyolefin materials. Silane cross-linking can make polyolefin materials cross-linked at a lower temperature, which can improve production efficiency and reduce energy consumption to a certain extent.
[0004] Silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable materials combine the advantages of silane cross-linking technology and low-smoke halogen-free flame-retardant technology, and have certain comprehensive performance. However, the cracking problem of cable materials has always been a key problem that is difficult to improve, especially the anti-cracking problem under the combined effects of cold and hot shock and light radiation aging is a weak technical point, which needs further research and solution. Summary of the invention
[0005] In order to further improve the anti-cracking performance of cable materials under the combined effects of thermal shock and light radiation aging, the present application provides a silane cross-linked low-smoke halogen-free flame retardant polyolefin cable material for photovoltaic cables and a preparation method thereof.
[0006] In a first aspect, the present application provides a method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables, using the following technical solution: A method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables comprises the following steps: 1) Dissolve β-cyclodextrin and polyethylene glycol in a solvent, then add 2,5-furandicarboxylic acid, react under an inert gas, and remove the solvent to obtain a precursor; 2) Sodium alginate, sepiolite and water are mixed to prepare a base liquid, acrylic acid, ethyl acrylate and a surfactant are added to the base liquid and mixed evenly, and then a polymerization initiator is added to react for 3-5 hours, and the obtained solid is washed with ethanol and deionized water, dried and ground to obtain an adsorbent material, and then the adsorbent material, maleimide and dimethyl sulfoxide are mixed evenly to obtain a delivery complex; 3) 30-60 parts of ethylene-vinyl acetate copolymer, 15-40 parts of metallocene polyethylene, 15-35 parts of compatibilizer, 130-200 parts of flame retardant, 3.5-7 parts of precursor, 0.05-0.2 parts of antioxidant, 2-5 parts of lubricant, 0.2-1 parts of dispersant, 1.5-3 parts of initiator, 0.05-0.3 parts of vulcanizing agent are mixed, and then mixed, extruded, and granulated to obtain material A; 4) 65-90 parts of ethylene-vinyl acetate copolymer, 15-25 parts of compatibilizer, 20-30 parts of delivery compound, 110-180 parts of flame retardant, 4-8 parts of antioxidant and 1-3 parts of catalyst are mixed, and then mixed, extruded and granulated to obtain material B; 5) Material A and material B are blended in a mass ratio of (80-90):(10-20) to prepare a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.
[0007] Preferably, the step 1) further includes at least one of the following technical features: 11) The solvent is one of DMF, acetonitrile and DMSO; 12) The mass ratio of β-cyclodextrin, polyethylene glycol and 2,5-furandicarboxylic acid is 1:(0.2-0.35):(1-1.2); 13) The reaction temperature is 5-25°C.
[0008] Preferably, the step 2) further includes at least one of the following technical features: 21) The mass ratio of sodium alginate, sepiolite and water is (0.05-0.1):(0.1-0.15):1; 22) The surfactant is an alkyl quaternary ammonium salt; 23) The polymerization initiator is a persulfate; 24) The average particle size of the adsorbent material is 50-200 μm; 25) The mass ratio of the adsorbent material, maleimide and dimethyl sulfoxide is 1:(1.5-2):(0.3-0.5).
[0009] Preferably, the alkyl quaternary ammonium salt is one of hexadecyl ammonium bromide, tetradecyl ammonium bromide and dodecyl ammonium bromide.
[0010] Preferably, in step 3) and / or step 4), the VA content of the ethylene-vinyl acetate copolymer is 26%-33%, and the melt index is 5-10 g / 10 min.
[0011] Preferably, in step 3) and / or step 4), the flame retardant is a mixture of one or more of aluminum hydroxide and magnesium hydroxide.
[0012] Preferably, in step 3) and / or step 4), the antioxidant is one of antioxidant 1010, antioxidant DLTP, antioxidant 1024, antioxidant 168, antioxidant 1076, etc., or a mixture of two or more thereof.
[0013] Preferably, the step 3) further includes at least one of the following technical features: 31) The lubricant is one or more of silicone, PE wax, fatty acid or fatty acid salt; 32) The initiator is one or more of vinyl trimethoxysilane A-171, vinyl triethoxysilane A-151, and γ-aminopropyl triethoxysilane KH-550; 33) The vulcanizing agent is one or more of dicumyl peroxide, tert-butyl peroxide, and benzoyl peroxide; 34) The dispersant is one or more of EBS, triethylhexyl phosphoric acid, and methyl amyl alcohol; 35) The metallocene polyethylene is a thermoplastic elastomer synthesized using metallocene as a catalyst, with a melt index greater than 10g / 10min and a Shore hardness less than 50D; 36) The compatibilizer is an ethylene-vinyl acetate copolymer graft material.
[0014] Preferably, in step 4), the catalyst is one or a mixture of two or more of tetrabutyl zirconate, dioctyl dibutyl tin, dibutyl tin diacetate, and dibutyl tin dilaurate; and the compatibilizer is an ethylene-vinyl acetate copolymer graft material.
[0015] In a second aspect, the present application provides a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables, which is prepared by the above-mentioned preparation method.
[0016] In summary, this application has the following beneficial effects: 1. This application uses a mixture of material A and material B. The prepared cable material has good mechanical properties, electrical properties, heat resistance and flame retardancy, and good flexibility, which can meet the use requirements of photovoltaic cables in harsh environments such as high and low temperatures and high light radiation. This application adds a precursor to material A. During the preparation of material A, the precursor is evenly dispersed in the polymer system of material A. The β-cyclodextrin in the precursor forms several cyclic sites on the polyethylene glycol molecular chain, and then 2,5-furandicarboxylic acid is grafted to the cyclic sites, thereby forming dynamic cross-linking sites in the cable material, which plays a very good molecular slip effect and greatly improves the toughness and crack resistance of the cable material.
[0017] 2. The present application adds a delivery complex to material B, and utilizes the mechanical locking effect of the porous adsorption material to enhance the compatibility between the delivery complex and the cable material. Meanwhile, in the subsequent fusion process of material A and material B, with the assistance of dimethyl sulfoxide, the delivery complex can slowly release maleimide molecules. A large number of maleimide molecules will form dynamic crosslinks with 2,5-furandicarboxylic acid on the cyclic sites, forming supramolecular effects under light radiation or a temperature environment of 50-70°C, so that the cable material undergoes dynamic elastic cycles under the superposition of low temperature, high temperature and light radiation, and can effectively release and absorb the internal stress of the material, thereby enhancing the anti-cracking performance of the cable material under the superposition of cold and hot shocks and light radiation aging within a certain period of time.
[0018] 3. The silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables prepared by the preparation method of the present application can be used in cable manufacturing in the photovoltaic industry, providing safe and reliable insulation and sheath materials for power transmission in photovoltaic systems. The prepared cables have a smooth, soft and crack-resistant surface and good overall performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM image of the adsorption material prepared in Example 1 of the present application.
[0020] Figure 2 This is a data graph of the anti-cracking performance of the silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable materials for photovoltaic cables of Examples 1-3 of the present application and Comparative Examples 1-2 under the combined effects of cold and hot shock and light radiation aging. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments.
[0022] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0023] After a large number of experiments, the inventors of the present application have constructed a dynamic cross-linking system in the cable material, thereby greatly improving the anti-cracking performance of the cable material under the superposition of complex environments.
[0024] The present application provides a method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables, which adopts the following technical scheme: A method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables comprises the following steps: 1) Dissolve β-cyclodextrin and polyethylene glycol in a solvent, then add 2,5-furandicarboxylic acid, react under an inert gas, and remove the solvent to obtain a precursor; 2) Sodium alginate, sepiolite and water are mixed to prepare a base liquid, acrylic acid, ethyl acrylate and a surfactant are added to the base liquid and mixed evenly, and then a polymerization initiator is added to react for 3-5 hours, and the obtained solid is washed with ethanol and deionized water, dried and ground to obtain an adsorbent material, and then the adsorbent material, maleimide and dimethyl sulfoxide are mixed evenly to obtain a delivery complex; 3) 30-60 parts of ethylene-vinyl acetate copolymer, 15-40 parts of metallocene polyethylene, 15-35 parts of compatibilizer, 130-200 parts of flame retardant, 3.5-7 parts of precursor, 0.05-0.2 parts of antioxidant, 2-5 parts of lubricant, 0.2-1 parts of dispersant, 1.5-3 parts of initiator, 0.05-0.3 parts of vulcanizing agent are mixed, and then mixed, extruded, and granulated to obtain material A; 4) 65-90 parts of ethylene-vinyl acetate copolymer, 15-25 parts of compatibilizer, 20-30 parts of delivery compound, 110-180 parts of flame retardant, 4-8 parts of antioxidant and 1-3 parts of catalyst are mixed, and then mixed, extruded and granulated to obtain material B; 5) Material A and material B are blended in a mass ratio of (80-90):(10-20) to prepare a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.
[0025] Preferably, the step 1) further includes at least one of the following technical features: 11) The solvent is one of DMF, acetonitrile and DMSO; 12) The mass ratio of β-cyclodextrin, polyethylene glycol and 2,5-furandicarboxylic acid is 1:(0.2-0.35):(1-1.2); 13) The reaction temperature is 5-25°C.
[0026] In some specific embodiments, the solvent can be DMF, acetonitrile or DMSO. Under normal circumstances, when the solvent is DMF, better experimental results can be obtained. In some specific embodiments, the mass ratio of β-cyclodextrin, polyethylene glycol, and 2,5-furandicarboxylic acid can be 1:0.2:1, 1:0.35:1.2, 1:0.2:12, 1:0.35:1, 1:0.25:1.2, 1:0.3:1.2, 1:0.25:1, 1:0.3:1, 1:0.2:1.1, 1:0.25:1.1, 1:0.3:1.1 or 1:0.35:1.1. Under normal circumstances, when the mass ratio of β-cyclodextrin, polyethylene glycol, and 2,5-furandicarboxylic acid is 1:0.25:1.1, better experimental results can be obtained. In some specific embodiments, the reaction temperature can be 5°C, 10°C, 15°C, 20°C, 22°C, or 25°C. Generally, better experimental results can be obtained when the reaction temperature is controlled at 10°C and 15°C.
[0027] Preferably, the step 2) further includes at least one of the following technical features: 21) The mass ratio of sodium alginate, sepiolite and water is (0.05-0.1):(0.1-0.15):1; 22) The surfactant is an alkyl quaternary ammonium salt; 23) The polymerization initiator is a persulfate; 24) The average particle size of the adsorbent material is 50-200 μm; 25) The mass ratio of the adsorbent material, maleimide and dimethyl sulfoxide is 1:(1.5-2):(0.3-0.5).
[0028] In some embodiments, the alkyl quaternary ammonium salt is one of hexadecyl ammonium bromide, tetradecyl ammonium bromide, and dodecyl ammonium bromide. More preferably, the alkyl quaternary ammonium salt is hexadecyl ammonium bromide.
[0029] In some specific embodiments, the mass ratio of sodium alginate, sepiolite, and water can be 0.05:0.1:1, 0.1:0.15:1, 0.05:0.15:1, 0.1:0.1:1, 0.075:0.1:1, 0.075:0.15:1, 0.05:0.12:1, 0.075:0.12:1, 0.05:0.13:1, 0.075:0.13:1, 0.075:0.135:1. Generally, when the mass ratio of sodium alginate, sepiolite, and water is 0.075:0.12:1, the experimental effect is best. In some specific embodiments, the persulfate can be ammonium persulfate, sodium persulfate, or potassium persulfate. In some specific embodiments, the mass ratio of the adsorbent material, maleimide, and dimethyl sulfoxide can be 1:1.5:0.3, 1:2:0.5, 1:1.5:0.5, 1:1.5:0.35, 1:1.5:0.4, 1:1.5:0.45, 1:1.8:0.3, 1:1.8:0.35, 1:1.5:0.45, 1:1.8:0.45, 1:2:0.45, 1:1.75:0.35, 1:1.75:0.4, more preferably, the mass ratio of the adsorbent material, maleimide, and dimethyl sulfoxide is 1:1.65:0.35.
[0030] Preferably, in step 3) and / or step 4), the VA content of the ethylene-vinyl acetate copolymer is 26%-33%, and the melt index is 5-10 g / 10 min.
[0031] Preferably, in step 3) and / or step 4), the flame retardant is a mixture of one or more of aluminum hydroxide and magnesium hydroxide.
[0032] Preferably, in step 3) and / or step 4), the antioxidant is one of antioxidant 1010, antioxidant DLTP, antioxidant 1024, antioxidant 168, antioxidant 1076, etc., or a mixture of two or more thereof.
[0033] Preferably, the step 3) further includes at least one of the following technical features: 31) The lubricant is one or more of silicone, PE wax, fatty acid or fatty acid salt; 32) The initiator is one or more of vinyl trimethoxysilane A-171, vinyl triethoxysilane A-151, and γ-aminopropyl triethoxysilane KH-550; 33) The vulcanizing agent is one or more of dicumyl peroxide, tert-butyl peroxide, and benzoyl peroxide; 34) The dispersant is one or more of EBS, triethylhexyl phosphoric acid, and methyl amyl alcohol; 35) The metallocene polyethylene is a thermoplastic elastomer synthesized using metallocene as a catalyst, with a melt index greater than 10g / 10min and a Shore hardness less than 50D; 36) The compatibilizer is an ethylene-vinyl acetate copolymer graft material.
[0034] Preferably, in step 4), the catalyst is one or a mixture of two or more of tetrabutyl zirconate, dioctyl dibutyl tin, dibutyl tin diacetate, and dibutyl tin dilaurate; and the compatibilizer is an ethylene-vinyl acetate copolymer graft material. Example 1
[0035] The method for preparing the silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables of this embodiment comprises the following steps: 1) Add DMF to a reactor equipped with a stirrer, a thermometer, and a feeder, then add β-cyclodextrin and polyethylene glycol and stir until the materials are completely dissolved, then maintain the reaction temperature range at 10-15°C, add an appropriate amount of catalyst, and slowly add 2,5-furandicarboxylic acid through the feeder, control the mass ratio of β-cyclodextrin, polyethylene glycol, and 2,5-furandicarboxylic acid to be 1:0.25:1.1, and react the reaction system under inert gas protection for 6 hours, and remove DMF to obtain a precursor; 2) Sodium alginate, sepiolite and water are placed in a stirring tank at a mass ratio of 0.075:0.12:1 and mixed evenly to obtain a base liquid, and then the base liquid is transferred to a reactor, and then acrylic acid, ethyl acrylate and a surfactant are added to the base liquid and mixed evenly, wherein the amount of acrylic acid added is 1 / 2 of the mass of sepiolite, the amount of ethyl acrylate added is 1 / 3 of the mass of sodium alginate, and the surfactant is hexadecyl ammonium bromide, and then ammonium persulfate and sodium sulfite are added to react for 4 hours, and the obtained solid is washed with ethanol and deionized water, and dried and ground to obtain an adsorbent material with an average particle size of 150 μm, and then the adsorbent material, maleimide and dimethyl sulfoxide are mixed evenly at a mass ratio of 1:1.65:0.35 to obtain a delivery complex; 3) Accurately weigh 45kg of ethylene-vinyl acetate copolymer, 35kg of metallocene polyethylene, 20kg of compatibilizer, 140kg of flame retardant, 5.5kg of precursor, 0.06kg of antioxidant, 1.8kg of lubricant, and 0.3kg of dispersant, and mix them in an internal mixer until they are lumped at 145-165℃. Pour them out, and then lift them to the double-cone feeding hopper with an elevator. Use a double-stage twin-screw extruder for plasticization and extrusion. The plasticization temperature is controlled at 100-140℃. After hot cutting and granulation, air cooling is performed. After the masterbatch of material A is obtained after vibrating screen sorting; the masterbatch of material A is dried in a dryer at 60°C for three hours, and directly put into a weight loss scale for metering and feeding; 2kg of initiator and 0.1kg of vulcanizer are weighed and mixed, and then added into the liquid weight loss scale for metering and feeding; the mixture of the masterbatch of material A, the initiator and the vulcanizer is accurately fed through a weight loss scale, plasticized in a twin screw at a temperature of 100-140°C, extruded, cooled by water drawing, air-dried and pelletized, and then deeply dried to obtain material A; 4) Accurately weigh 88kg of ethylene-vinyl acetate copolymer, 12kg of compatibilizer, 25kg of delivery compound, 140kg of flame retardant, and 4.6kg of antioxidant, use a banbury mixer to knead until 140-160℃ to form a mass, then pour it out, use an elevator to lift it to a double-cone feeding hopper, use a double-stage twin-screw extruder unit for plasticization and extrusion, the plasticization temperature is 100-135℃, and after hot cutting granulation, air cooling, and vibration screening, obtain the B material masterbatch; Pour the masterbatch of material B and 1.2kg of catalyst into a low-speed mixer and mix for 3-5 minutes. After discharging the material, add it into the hopper of the twin screw extruder. The overall plasticizing temperature of the twin screw extruder is 90-130℃. After plasticizing and extruding by the twin screw extruder, cool the strips and dry them to obtain material B. 5) Material A and material B are blended in a mass ratio of 90:10 to prepare a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.
[0036] Among them, in material A, the antioxidant is composed of antioxidant 1010 and antioxidant DLTP in a mass ratio of 1:1, the lubricant is composed of silicone and PE wax in a mass ratio of 1:1, the dispersant is triethylhexyl phosphoric acid, the vulcanizer is diisopropylbenzene peroxide, the compatibilizer is ethylene-vinyl acetate copolymer grafted material, and the flame retardant is aluminum hydroxide.
[0037] In material B, the antioxidant is composed of antioxidant AT-10, antioxidant DLTP, antioxidant 168 and antioxidant 1024 in a mass ratio of 15:15:8:8. The catalyst is tetrabutyl zirconate, the compatibilizer is ethylene-vinyl acetate copolymer graft material, and the flame retardant is aluminum hydroxide. Example 2
[0038] The method for preparing the silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables of this embodiment comprises the following steps: 1) Add DMF to a reactor equipped with a stirrer, a thermometer, and a feeder, then add β-cyclodextrin and polyethylene glycol and stir until the materials are completely dissolved, then maintain the reaction temperature range at 10-15°C, add an appropriate amount of catalyst, and slowly add 2,5-furandicarboxylic acid through the feeder, control the mass ratio of β-cyclodextrin, polyethylene glycol, and 2,5-furandicarboxylic acid to be 1:0.25:1.1, and react the reaction system under inert gas protection for 6 hours, and remove DMF to obtain a precursor; 2) Sodium alginate, sepiolite and water are placed in a stirring tank at a mass ratio of 0.075:0.12:1 and mixed evenly to obtain a base liquid, and then the base liquid is transferred to a reactor, and then acrylic acid, ethyl acrylate and a surfactant are added to the base liquid and mixed evenly, wherein the amount of acrylic acid added is 1 / 2 of the mass of sepiolite, the amount of ethyl acrylate added is 1 / 3 of the mass of sodium alginate, and the surfactant is hexadecyl ammonium bromide, and then ammonium persulfate and sodium sulfite are added to react for 4 hours, and the obtained solid is washed with ethanol and deionized water, and dried and ground to obtain an adsorbent material with an average particle size of 150 μm, and then the adsorbent material, maleimide and dimethyl sulfoxide are mixed evenly at a mass ratio of 1:1.65:0.35 to obtain a delivery complex; 3) Accurately weigh 50kg of ethylene-vinyl acetate copolymer, 25kg of metallocene polyethylene, 25kg of compatibilizer, 150kg of flame retardant, 7kg of precursor, 0.07kg of antioxidant, 2.8kg of lubricant, and 0.4kg of dispersant, and place them in an internal mixer and mix them until they reach 145-165℃ and form a mass. Pour them out and then lift them to a double-cone feeding hopper with an elevator. Use a double-stage twin-screw extruder for plasticization and extrusion. The plasticization temperature is controlled at 100-140℃. After hot cutting and granulation, they are cooled by air conveying. After vibrating screen sorting, the masterbatch of material A is obtained; the masterbatch of material A is dried in a dryer at 60°C for three hours, and directly put into a weight loss scale for metering and feeding; 2.2 kg of initiator and 0.12 kg of vulcanizer are weighed and mixed, and then added into the liquid weight loss scale for metering and feeding; the mixture of the masterbatch of material A, the initiator and the vulcanizer is accurately fed through a weight loss scale, plasticized in a twin screw at a temperature of 100-140°C, extruded, cooled by water drawing, air-dried and pelletized, and then deeply dried to obtain material A; 4) Accurately weigh 86kg of ethylene-vinyl acetate copolymer, 14kg of compatibilizer, 30kg of delivery compound, 150kg of flame retardant, and 5.6kg of antioxidant, use a banbury mixer to knead until 140-160℃ to form a mass, then pour it out, use an elevator to lift it to a double-cone feeding hopper, use a double-stage twin-screw extruder unit for plasticization and extrusion, the plasticization temperature is 100-135℃, and after hot cutting granulation, air cooling, and vibration screening, obtain the B material masterbatch; Pour the masterbatch of material B and 1.5kg of catalyst into a low-speed mixer and mix for 3-5 minutes. After discharging the materials, add them into the hopper of the twin screw extruder. The overall plasticizing temperature of the twin screw extruder is 90-130℃. After plasticizing and extruding by the twin screw extruder, cool the strips and dry them to obtain material B. 5) Material A and material B were blended in a mass ratio of 85:15 to prepare a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.
[0039] Among them, in material A, the antioxidant is composed of antioxidant 1010 and antioxidant DLTP in a mass ratio of 3:4, the lubricant is composed of silicone and PE wax in a mass ratio of 5:2, the dispersant is EBS, the vulcanizer is benzoyl peroxide, the compatibilizer is ethylene-vinyl acetate copolymer grafted material, and the flame retardant is aluminum hydroxide.
[0040] In material B, the antioxidant is composed of antioxidant AT-10, antioxidant DLTP, antioxidant 168 and antioxidant 1024 in a mass ratio of 9:9:5:5. The catalyst is tetrabutyl zirconate, the compatibilizer is ethylene-vinyl acetate copolymer graft material, and the flame retardant is aluminum hydroxide. Example 3
[0041] The method for preparing the silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables of this embodiment comprises the following steps: 1) Add DMF to a reactor equipped with a stirrer, a thermometer, and a feeder, then add β-cyclodextrin and polyethylene glycol and stir until the materials are completely dissolved, then maintain the reaction temperature range at 10-15°C, add an appropriate amount of catalyst, and slowly add 2,5-furandicarboxylic acid through the feeder, control the mass ratio of β-cyclodextrin, polyethylene glycol, and 2,5-furandicarboxylic acid to be 1:0.25:1.1, and react the reaction system under inert gas protection for 6 hours, and remove DMF to obtain a precursor; 2) Sodium alginate, sepiolite and water are placed in a stirring tank at a mass ratio of 0.075:0.12:1 and mixed evenly to obtain a base liquid, and then the base liquid is transferred to a reactor, and then acrylic acid, ethyl acrylate and a surfactant are added to the base liquid and mixed evenly, wherein the amount of acrylic acid added is 1 / 2 of the mass of sepiolite, the amount of ethyl acrylate added is 1 / 3 of the mass of sodium alginate, and the surfactant is hexadecyl ammonium bromide, and then ammonium persulfate and sodium sulfite are added to react for 4 hours, and the obtained solid is washed with ethanol and deionized water, and dried and ground to obtain an adsorbent material with an average particle size of 150 μm, and then the adsorbent material, maleimide and dimethyl sulfoxide are mixed evenly at a mass ratio of 1:1.65:0.35 to obtain a delivery complex; 3) Accurately weigh 55kg of ethylene-vinyl acetate copolymer, 20kg of metallocene polyethylene, 25kg of compatibilizer, 170kg of flame retardant, 3.5kg of precursor, 0.07kg of antioxidant, 3.2kg of lubricant, and 0.5kg of dispersant, and place them in an internal mixer and mix them until they reach 145-165℃, then pour them out and lift them into a double-cone feeding hopper with an elevator. Use a double-stage twin-screw extruder for plasticization and extrusion. The plasticization temperature is controlled at 100-140℃, and then they are granulated by hot cutting and cooled by air conveying. , after vibrating screen sorting, obtain the masterbatch of material A; dry the masterbatch of material A in a dryer at 60°C for three hours, and directly put it into a weight loss scale for metering and feeding; weigh 2.4kg of initiator and 0.14kg of vulcanizer, mix them, and add them into the liquid weight loss for metering and feeding; accurately feed the mixture of masterbatch of material A, initiator and vulcanizer through a weight loss scale, plasticize in a twin screw at a temperature of 100-140°C, and after extrusion, cool it through water drawing, air dry and pelletize it, and then obtain material A through deep drying; 4) Accurately weigh 80kg of ethylene-vinyl acetate copolymer, 20kg of compatibilizer, 20kg of delivery compound, 160kg of flame retardant, and 4.4kg of antioxidant, use a banbury mixer to knead until 140-160℃ to form a mass, then pour it out, use an elevator to lift it to a double-cone feeding hopper, use a double-stage twin-screw extruder unit for plasticization and extrusion, the plasticization temperature is 100-135℃, and after hot cutting granulation, air cooling, and vibration screening, obtain the B material masterbatch; Pour the masterbatch of material B and 1.8kg of catalyst into a low-speed mixer and mix for 3-5 minutes. After discharging the material, add it into the hopper of the twin screw extruder. The overall plasticizing temperature of the twin screw extruder is 90-130℃. After plasticizing and extruding by the twin screw extruder, cool the strips and dry them to obtain material B. 5) Material A and material B are blended in a mass ratio of 90:10 to prepare a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.
[0042] Among them, in material A, the antioxidant is composed of antioxidant 1010 and antioxidant DLTP in a mass ratio of 3:4, the lubricant is composed of silicone and PE wax in a mass ratio of 5:2, the dispersant is EBS, the vulcanizer is benzoyl peroxide, the compatibilizer is ethylene-vinyl acetate copolymer grafted material, and the flame retardant is aluminum hydroxide.
[0043] In material B, the antioxidant is composed of antioxidant AT-10, antioxidant DLTP, antioxidant 168 and antioxidant 1024 in a mass ratio of 9:9:5:5. The catalyst is tetrabutyl zirconate, the compatibilizer is ethylene-vinyl acetate copolymer graft material, and the flame retardant is aluminum hydroxide.
[0044] Comparative Example 1 The preparation method of the silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables of this comparative example comprises the following steps: 1) Accurately weigh 45kg of ethylene-vinyl acetate copolymer, 35kg of metallocene polyethylene, 20kg of compatibilizer, 140kg of flame retardant, 0.06kg of antioxidant, 1.8kg of lubricant, and 0.3kg of dispersant, and place them in an internal mixer and mix them until they reach 145-165℃ and form a mass. Then pour them out and lift them to a double-cone feeding hopper with an elevator. Use a double-stage twin-screw extruder for plasticization and extrusion. The plasticization temperature is controlled at 100-140℃. After hot cutting and granulation, air cooling, vibration After screening and sorting, the masterbatch of material A is obtained; the masterbatch of material A is dried in a dryer at 60°C for three hours, and directly put into a weight loss scale for metering and feeding; 2kg of initiator and 0.1kg of vulcanizer are weighed and mixed, and then added into the liquid weight loss scale for metering and feeding; the mixture of the masterbatch of material A, the initiator and the vulcanizer is accurately fed through a weight loss scale, plasticized in a twin screw at a temperature of 100-140°C, extruded, cooled by water drawing, air-dried and pelletized, and then deeply dried to obtain material A; 2) Accurately weigh 88kg of ethylene-vinyl acetate copolymer, 12kg of compatibilizer, 140kg of flame retardant, and 4.6kg of antioxidant, use a banbury mixer to knead until 140-160℃ to form a mass, then pour it out, use an elevator to lift it to a double-cone feeding hopper, use a double-stage twin-screw extruder unit for plasticization and extrusion, the plasticization temperature is 100-135℃, and after hot cutting granulation, air cooling, and vibration screening, obtain the B material masterbatch; Pour the masterbatch of material B and 1.2kg of catalyst into a low-speed mixer and mix for 3-5 minutes. After discharging the material, add it into the hopper of the twin screw extruder. The overall plasticizing temperature of the twin screw extruder is 90-130℃. After plasticizing and extruding by the twin screw extruder, cool the strips and dry them to obtain material B. 3) Material A and material B were blended in a mass ratio of 80:20 to prepare a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.
[0045] Among them, in material A, the antioxidant is composed of antioxidant 1010 and antioxidant DLTP in a mass ratio of 1:1, the lubricant is composed of silicone and PE wax in a mass ratio of 1:1, the dispersant is triethylhexyl phosphoric acid, the vulcanizer is diisopropylbenzene peroxide, the compatibilizer is ethylene-vinyl acetate copolymer grafted material, and the flame retardant is aluminum hydroxide.
[0046] In material B, the antioxidant is composed of antioxidant AT-10, antioxidant DLTP, antioxidant 168 and antioxidant 1024 in a mass ratio of 15:15:8:8. The catalyst is tetrabutyl zirconate, the compatibilizer is ethylene-vinyl acetate copolymer graft material, and the flame retardant is aluminum hydroxide.
[0047] Comparative Example 2 The preparation method of the silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables of this embodiment of the comparative example comprises the following steps: 1) Accurately weigh 45kg of ethylene-vinyl acetate copolymer, 35kg of metallocene polyethylene, 20kg of compatibilizer, 140kg of flame retardant, 3.5kg of β-cyclodextrin, 2kg of polyethylene glycol, 0.06kg of antioxidant, 1.8kg of lubricant, and 0.3kg of dispersant, and mix them in an internal mixer until they reach 145-165℃ and form a mass. Then pour it out and lift it to a double-cone feeding hopper with an elevator. Use a double-stage twin-screw extruder for plasticization and extrusion. The plasticization temperature is controlled at 100-140℃. After hot cutting, The masterbatch of material A is obtained after being granulated, cooled by air conveying, and selected by vibration screen; the masterbatch of material A is dried in a dryer at 60°C for three hours, and directly put into a weight loss scale for metering and feeding; 2kg of initiator and 0.1kg of vulcanizer are weighed and mixed, and then added into the liquid weight loss scale for metering and feeding; the mixture of the masterbatch of material A, the initiator and the vulcanizer is accurately fed through a weight loss scale, plasticized in a twin screw at a temperature of 100-140°C, extruded, cooled by water drawing, air dried and pelletized, and then deeply dried to obtain material A; 2) Accurately weigh 88kg of ethylene-vinyl acetate copolymer, 12kg of compatibilizer, 15kg of sodium alginate, 5kg of dimethyl sulfoxide, 5kg of maleimide, 140kg of flame retardant, and 4.6kg of antioxidant, use a banbury mixer to knead until 140-160℃ to form a mass, then pour it out, use an elevator to lift it to a double-cone feeding hopper, use a double-stage twin-screw extruder unit for plasticization and extrusion, the plasticization temperature is 100-135℃, and after hot cutting granulation, air cooling, and vibration screening, obtain the B material masterbatch; Pour the masterbatch of material B and 1.2kg of catalyst into a low-speed mixer and mix for 3-5 minutes. After discharging the material, add it into the hopper of the twin screw extruder. The overall plasticizing temperature of the twin screw extruder is 90-130℃. After plasticizing and extruding by the twin screw extruder, cool the strips and dry them to obtain material B. 3) Material A and material B were blended in a mass ratio of 80:20 to prepare a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.
[0048] Among them, in material A, the antioxidant is composed of antioxidant 1010 and antioxidant DLTP in a mass ratio of 1:1, the lubricant is composed of silicone and PE wax in a mass ratio of 1:1, the dispersant is triethylhexyl phosphoric acid, the vulcanizer is diisopropylbenzene peroxide, the compatibilizer is ethylene-vinyl acetate copolymer grafted material, and the flame retardant is aluminum hydroxide.
[0049] In material B, the antioxidant is composed of antioxidant AT-10, antioxidant DLTP, antioxidant 168 and antioxidant 1024 in a mass ratio of 15:15:8:8. The catalyst is tetrabutyl zirconate, the compatibilizer is ethylene-vinyl acetate copolymer graft material, and the flame retardant is aluminum hydroxide.
[0050] Performance testing 1. Comprehensive performance tests were conducted on the silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable materials for photovoltaic cables of Examples 1-3 and Comparative Examples 1-2. The test results are shown in the following table.
[0051]
[0052] 2. The adsorption material prepared in Example 1 was tested by scanning electron microscope. The results are as follows: Figure 1 As shown, it can be seen that the porous adsorption material prepared in the present application has a large specific surface area, a large adsorption capacity, and a strong bonding force with the cable material.
[0053] 3. Take the silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables of Examples 1-3 and Comparative Examples 1-2, and make strip samples with the dimensions of: 15 cm in length, 5 cm in width, and 0.5 cm in thickness. Place the strip samples in a high and low temperature aging test chamber, first keep them at -20°C for 0.5 h, then keep them at 120°C for 1.5 h, and then put them in a hernia lamp weathering test chamber for light radiation for 5 h (wavelength 300-400nm, 60W / ㎡, humidity 50%), with one cycle as one cycle, and then use a universal testing machine to test the change trend of elastic recovery rate with the number of cycles, so as to evaluate the anti-cracking performance of the cable material under the superposition environment of cold and hot shock and light radiation aging. The results are as follows: Figure 2 As shown, the horizontal axis is the number of cycles and the vertical axis is the elastic recovery rate.
[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables, characterized in that: The steps include: 1) Dissolve β-cyclodextrin and polyethylene glycol in a solvent, then add 2,5-furandicarboxylic acid, react under an inert gas, and remove the solvent to obtain a precursor; 2) Sodium alginate, sepiolite and water are mixed to prepare a base liquid, acrylic acid, ethyl acrylate and a surfactant are added to the base liquid and mixed evenly, and then a polymerization initiator is added to react for 3-5 hours, and the obtained solid is washed with ethanol and deionized water, dried and ground to obtain an adsorbent material, and then the adsorbent material, maleimide and dimethyl sulfoxide are mixed evenly to obtain a delivery complex; 3) 30-60 parts of ethylene-vinyl acetate copolymer, 15-40 parts of metallocene polyethylene, 15-35 parts of compatibilizer, 130-200 parts of flame retardant, 3.5-7 parts of precursor, 0.05-0.2 parts of antioxidant, 2-5 parts of lubricant, 0.2-1 parts of dispersant, 1.5-3 parts of initiator, 0.05-0.3 parts of vulcanizing agent are mixed, and then mixed, extruded, and granulated to obtain material A; 4) 65-90 parts of ethylene-vinyl acetate copolymer, 15-25 parts of compatibilizer, 20-30 parts of delivery compound, 110-180 parts of flame retardant, 4-8 parts of antioxidant and 1-3 parts of catalyst are mixed, and then mixed, extruded and granulated to obtain material B; 5) Material A and material B are blended in a mass ratio of (80-90):(10-20) to prepare a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables.
2. The method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 1, characterized in that: The step 1) further includes at least one of the following technical features: 11) The solvent is one of DMF, acetonitrile and DMSO; 12) The mass ratio of β-cyclodextrin, polyethylene glycol and 2,5-furandicarboxylic acid is 1:(0.2-0.35):(1-1.2); 13) The reaction temperature is 5-25°C.
3. The method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 1, characterized in that: The step 2) further includes at least one of the following technical features: 21) The mass ratio of sodium alginate, sepiolite and water is (0.05-0.1):(0.1-0.15):1; 22) The surfactant is an alkyl quaternary ammonium salt; 23) The polymerization initiator is a persulfate; 24) The average particle size of the adsorbent material is 50-200 μm; 25) The mass ratio of the adsorbent material, maleimide and dimethyl sulfoxide is 1:(1.5-2):(0.3-0.5).
4. The method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 3, characterized in that: The alkyl quaternary ammonium salt is one of hexadecyl ammonium bromide, tetradecyl ammonium bromide and dodecyl ammonium bromide.
5. The method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 1, characterized in that: In step 3) and / or step 4), the VA content of the ethylene-vinyl acetate copolymer is 26%-33%, and the melt index is 5-10 g / 10 min.
6. The method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 1, characterized in that: In step 3) and / or step 4), the flame retardant is a mixture of one or more of aluminum hydroxide and magnesium hydroxide.
7. The method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 1, characterized in that: In step 3) and / or step 4), the antioxidant is one of antioxidant 1010, antioxidant DLTP, antioxidant 1024, antioxidant 168, antioxidant 1076, etc., or a mixture of two or more thereof.
8. The method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 1, characterized in that: The step 3) further includes at least one of the following technical features: 31) The lubricant is one or more of silicone, PE wax, fatty acid or fatty acid salt; 32) The initiator is one or more of vinyl trimethoxysilane A-171, vinyl triethoxysilane A-151, and γ-aminopropyl triethoxysilane KH-550; 33) The vulcanizing agent is one or more of dicumyl peroxide, tert-butyl peroxide, and benzoyl peroxide; 34) The dispersant is one or more of EBS, triethylhexyl phosphoric acid, and methyl amyl alcohol; 35) The metallocene polyethylene is a thermoplastic elastomer synthesized using metallocene as a catalyst, with a melt index greater than 10g / 10min and a Shore hardness less than 50D; 36) The compatibilizer is an ethylene-vinyl acetate copolymer graft material.
9. The method for preparing a silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables according to claim 1, characterized in that: In the step 4), the catalyst is one or a mixture of two or more of tetrabutyl zirconate, dioctyl dibutyl tin, dibutyl tin diacetate, and dibutyl tin dilaurate; and the compatibilizer is an ethylene-vinyl acetate copolymer graft material.
10. A silane cross-linked low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic cables, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
2,5-furan dicarboxylate derivatives, and use thereof as plasticizers
CN102596927A
Cracking-resistant thermoplastic low-smoke halogen-free flame-retardant polyolefin cable material
CN103030917A
Halogen-free flame retardant organosilane self-crosslinked polyolefin cable material and preparation method thereof
CN103724759A
In-situ mineralized reinforced composite hydrogel and preparation method thereof
CN104177636A
Preparation method of microporous polycaprolactone-polyacrylic sodium alginate resin
CN104558676A
Cited By
High-flame-retardant low-smoke halogen-free polyolefin cable material and preparation method thereof
CN119955202A
Weather-proof silane self-crosslinking low-smoke halogen-free flame-retardant polyolefin cable material
CN121226893A